A Look into Sociology, or a Look into the Common - Daujotytė, Viktorija (Sociologija. Mintis ir veiksmas, 1997)
The article presented in the first issue of the journal discuses the relationship between sociology and the social reality. It is emphasized that the central task of sociology is to orient among the constantly changing social situations. Such a task requires to discuss the links between sociology and literature.
Keywords: sociology; social reality; literature